Spontaneous Isolated Infection of the Subacromial Bursa. (29th July 2013) - Khan, Hayat; Al-Tawil, Karam
Abstract : Isolated infection of the subacromial bursa is a rare entity. We present the case of a previously fit man who was found to have staphylococcal infection of the sub-acromial bursa, without an obvious precipitant. Preoperative MRI scanning determined the specific locus of infection, and the patient was successfully treated with arthroscopic washout of the sub-acromial bursa followed by empirical antibiotic therapy.